Political conservatism and the exploitation of nonhuman animals: An application of system justification theory. (September 2019) - Hoffarth, Mark R.; Azevedo, Flávio; Jost, John T.
Many people in Western societies tolerate the mistreatment of nonhuman animals, despite obvious ethical concerns about the injustice of animal suffering and exploitation. In three studies, we applied system justification theory to examine the ideological basis of human–animal relations. In Studies 1a and 1b, we showed in both a large convenience sample ( N = 2, 119) and a nationally representative sample in the US ( N = 1, 500) that economic system justification uniquely explained the relationship between political conservatism and animal welfare attitudes even after adjusting for social dominance orientation. In Study 2, we replicated and extended these findings using more elaborate measures of animal welfare attitudes in the context of an MTurk sample of U.S. respondents ( N = 395). Specifically, we found that conservatism was associated with less support for animal welfare and greater endorsement of speciesism (the belief that humans are morally superior to nonhuman animals) and that individual differences in economic system justification mediated these associations. We discuss several ways in which system justification theory may inform interventions designed to promote support for animal welfare in society at large.